Efektivitas Pembelajaran Berbasis Proyek dalam Meningkatkan Keterampilan Menulis pada Pembelajar Bahasa Inggris - Akhmad Nuris Hidayat; Lutfiah; Rizal Akillah (Mastery: Master of English Language Journal, 2024)
This study looks into how English Language Learners' (ELLs') writing abilities are affected by project-based learning (PBL). The study used a sample of 70 ELL students from two classes which uses a quantitative research design. The stu-dents were split into two groups: the experimental group participated in PBL activities, while the control group got traditional training. Pre- and post-tests were used to track gains in a number of writing-related areas, such as vocabu-lary, grammar, coherence, and overall writing quality. According to the findings, students in the experimental group improved their writing considerably more than those in the control group. The PBL technique was very successful in improving students' capacity to write cohesive essays and employ a variety of terminology, according to statistical analysis. When partici-pating in PBL activities, students also reported being more motivated and en-gaged in their writing assignments. These results imply that PBL is an effective teaching strategy for ELL students' writing ability development, providing an immersive and participatory learning environment that may be absent from traditional methods. According to the study, including PBL into ELL curricula can improve students' writing and language skills.